2018
DOI: 10.1007/s10897-017-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Test Reporting and Counseling for Melanoma Risk in Minors May Improve Sun Protection Without Inducing Distress

Abstract: Genetic testing of minors is advised only for conditions in which benefits of early intervention outweigh potential psychological harms. This study investigated whether genetic counseling and test reporting for the CDKN2A/p16 mutation, which confers highly elevated melanoma risk, improved sun protection without inducing distress. Eighteen minors (M = 12.4, SD = 1.9) from melanoma-prone families completed measures of protective behavior and distress at baseline, 1 week (distress only), 1 month, and 1 year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 35 publications
0
55
1
Order By: Relevance
“…Although the authors suggested that this small initial study provided support for the clinical usefulness of genetic testing and counseling for melanoma risk among minors from families with known familial predisposition mutations, they also noted the importance of confirming the findings in a much larger sample. 26 Although mutation-positive members of CDKN2A + families have an increased risk of melanoma, we recently reported that among American and Swedish CDKN2A + families, members who tested negative for their family's mutation remained at a moderately increased risk of melanoma. 27 Therefore, mutation-negative family members also should be encouraged to follow sun safety recommendations and practice skin self-examination in addition to being considered for continuing dermatologic surveillance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the authors suggested that this small initial study provided support for the clinical usefulness of genetic testing and counseling for melanoma risk among minors from families with known familial predisposition mutations, they also noted the importance of confirming the findings in a much larger sample. 26 Although mutation-positive members of CDKN2A + families have an increased risk of melanoma, we recently reported that among American and Swedish CDKN2A + families, members who tested negative for their family's mutation remained at a moderately increased risk of melanoma. 27 Therefore, mutation-negative family members also should be encouraged to follow sun safety recommendations and practice skin self-examination in addition to being considered for continuing dermatologic surveillance.…”
Section: Discussionmentioning
confidence: 93%
“…In a position paper published in 2015, the American Society of Human Genetics recommended the use of predictive genetic testing in minors only for conditions for which a clinical intervention could be delivered in childhood and for which the benefits of early intervention outweighed potential psychological harms. 25,26 Stump et al 26 recently investigated whether genetic counseling and test reporting for CDKN2A mutations improved sun protection without inducing distress. In a very small initial study of 9 carriers and 9 noncarriers, the authors reported significantly fewer sunburns and a greater percentage of individuals reporting sun protection adherence between baseline and 1 year after disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported psychological outcomes assessed included: generalised anxiety and depression [20][21][22][23][24][25][26]; melanoma-specific distress [20][21][22][23][24][25][26][27][28]; cancer (melanoma and pancreatic) worry/concern [24,[26][27][28]; and decision (for genetic testing) regret [20,[24][25][26]. Most studies utilised validated, widely accepted surveys such as the Hospital Anxiety and Depression Scale which includes two 7-item subscales to measure both anxiety and depression, and is widely used in research [29]; the Impact of Events Scale, which comprises 15 items to assess intrusive and avoidant cognitions and behaviours in respondents and has been used to measure disease-specific distress [30]; and the Multidimensional Impact of Cancer Risk Assessment scale, a 25-item survey that is commonly used to assess distress and uncertainty in people undergoing genetic testing [31].…”
Section: Adverse Psychological Outcomesmentioning
confidence: 99%
“…Most studies utilised validated, widely accepted surveys such as the Hospital Anxiety and Depression Scale which includes two 7-item subscales to measure both anxiety and depression, and is widely used in research [29]; the Impact of Events Scale, which comprises 15 items to assess intrusive and avoidant cognitions and behaviours in respondents and has been used to measure disease-specific distress [30]; and the Multidimensional Impact of Cancer Risk Assessment scale, a 25-item survey that is commonly used to assess distress and uncertainty in people undergoing genetic testing [31]. Other validated questionnaires were used to capture cancer worry [32][33][34], decision regret [35], mental health [36], anxiety and depression in adolescents [37,38], and lastly open-ended and semi-structured interviews were used in 3 studies [25,26,28].…”
Section: Adverse Psychological Outcomesmentioning
confidence: 99%
“…). In contrast, CDKN2A testing in high‐risk melanoma families has been associated with increased perceived control and a positive impact on screening adherence in carriers . If further quantitative studies demonstrate that genetic testing, education and counselling for melanoma have a positive impact on sun‐protective and surveillance behaviour in the general population, this could have implications for public health initiatives, particularly in Australia.…”
mentioning
confidence: 99%